Echocardiography and FDG-PET/CT scan in Gram-negative bacteremia and cardiovascular infections. Issue 6 (December 2021) - Dahl, Anders; Hernandez-Meneses, M.; Perissinotti, A.; Vidal, B.; Quintana, E.; Miro, Jose M.
Abstract : Purpose of review: Current evidence on cardiovascular infections in Gram-negative blood stream infections (GNBSI) with focus on the use of transesophageal echocardiography (TEE) and 18 F-Fluorodeoxyglucose - positron emission tomography/Computed tomography (FDG-PET/CT) in the diagnostic workup. Recent findings: Most evidence focuses on characteristics of diagnosed cardiovascular infections and the proportion caused by GNBSI. These proportions are low (1–5%) when it comes to native and prosthetic valve endocarditis as well as cardiac implantable electronic device (CIED) infections whereas the proportion of vascular graft infections caused by GNBSI seems substantially higher (30–40%). Information on the prevalence of cardiovascular infection in patients with GNBSI is limited to a few studies finding around 3% endocarditis in patients with GNBSI and a prosthetic heart valve and 4–16% device-related infection in patients with CIED and GNBSI. Summary: Patients with GNBSI and native or prosthetic valves should only undergo work-up for endocarditis (TEE and FDG-PET/CT) if they present GNBSI relapse or signs suggestive of endocarditis. CIED patients with GNBSI with Pseudomonas or Serratia spp. should undergo TEE and PET/CT because of the high prevalence of device-related infection. In other GNBs without IE suggestive signs, normal BSI treatment is reasonable and only cases with relapse need work-up. GNBSI in patients with vascular grafts should lead to consideration of PET/CT.